Intelligent communication and networking key technologies for manned/unmanned cooperation: states-of-the-art and trends - Hao YIN; Jibo WEI; Haitao ZHAO; Jiao ZHANG; Haijun WANG; Baoquan REN (Tongxin xuebao)
The intelligent communication and networking technologies for manned/unmanned cooperation was comprehensively surveyed.Firstly, the requirements on communication and networking were analyzed from the application scenarios of manned/unmanned cooperation.Then, in context of physical layer, link layer and network layer respectively, the key issues regarding channel modeling, waveform design, networking protocol and intelligent collaboration were analyzed.And the states-of-the-art in this research area and the characteristics of representative technologies were deeply studied.In the end, the possible development trends and promising technologies were prospected on the way to make the manned/unmanned cooperative communication and networking more intelligent, more efficient and more flexible.